2018
DOI: 10.1111/aogs.13288
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal vaccination against Group B streptococcus: attitudes of pregnant women and healthcare professionals in the UK towards participation in clinical trials and routine implementation

Abstract: Pregnant women and healthcare professionals were open to the idea of an antenatal Group B streptococcus vaccine and involvement in clinical trials of such a vaccine. Education and support from midwives would be key to successful implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Another important finding was that pregnant women of ethnic minorities were significantly less likely to accept vaccination than those identifying as 'White British'. Previous research has similarly demonstrated lower vaccine acceptance among these groups [23][24][25] , and these findings highlight the importance of taking into account possible cultural/religious and language barriers when counselling these women and producing educational materials. The underlying reasons for the difference in vaccine attitudes between ethnic groups remains a significant gap in our knowledge, and future studies in this specific area are needed.…”
Section: A C C E P T E Dmentioning
confidence: 55%
“…Another important finding was that pregnant women of ethnic minorities were significantly less likely to accept vaccination than those identifying as 'White British'. Previous research has similarly demonstrated lower vaccine acceptance among these groups [23][24][25] , and these findings highlight the importance of taking into account possible cultural/religious and language barriers when counselling these women and producing educational materials. The underlying reasons for the difference in vaccine attitudes between ethnic groups remains a significant gap in our knowledge, and future studies in this specific area are needed.…”
Section: A C C E P T E Dmentioning
confidence: 55%
“…Younger women (16-24 years), those of 21-30 weeks' gestation, and with experience of RSV were significantly more likely to participate in trials (OR: 1.42 [1.72-9.86]; OR: 2.29 [1.22-4.31]; OR: 9.07 [1.62-50.86], respectively). White-British women and those of [21][22][23][24][25][26][27][28][29][30] weeks' gestation were more likely to accept routinely-recommended vaccination (OR: 2.16 [1.07-4.13]; OR: 2.10 [1.07-4.13]).…”
Section: Resultsmentioning
confidence: 99%
“…We do note that those who perceived bronchiolitis as serious were significantly less likely to consider participating in an RSV trial, however it is possible that this is a result of confounding due to a lack of knowledge regarding bronchiolitis. It is also interesting to note that women of [21][22][23][24][25][26][27][28][29][30] weeks' gestation were significantly more accepting of both RSV trials and routine vaccination, perhaps due to a sense of reassurance following their 20-week anomaly scan and subsequent clinical review. Finally, the finding that women of ethnic minorities were less likely to accept routine RSV vaccination has been similarly observed in a number of previous studies of routinely-recommended vaccines [21][22][23] , yet the underlying reasons remain poorly understood, and may include cultural/religious differences, as well as language barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both vaccinations are currently under development. Knowledge about the two diseases is generally low amongst pregnant women, 30 but acceptance of a vaccine seems high for both diseases and amongst healthcare professionals 30,31 …”
Section: Future Developmentsmentioning
confidence: 99%